PRAKTIK KERJA INDUSTRI DAN BIMBINGAN KARIR TERHADAP KESIAPAN KERJA DI SMK NEGERI 1 SURAKARTA TAHUN AJARAN 2019/2020 - Ameylea Anggara; C. Dyah S. Indrawati; Anton Subarno (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2020)
The research aims to know (1) whether there is an effect of internship program towards work readiness of grade XII students at automation and office governance of vocational high school 1 surakarta (2) whether there is an effect of career guidance towards work readiness of grade XII students at automation and office governance of vocational high school 1 surakarta (3) whether there is an effect of internship program and career guidance towards work readiness of grade XII students at automation and office governance of vocational high school 1 Surakarta. This research is qualitative research. The population of research was grade XII students at automation and office governance vocational high school 1 surakarta which amounts to 102 students. The sampling technique uses proportional random sampling technique with amounts 81 students. The data collection method uses questionnaire and documentation. Data analysis was performed by validity test, reliability, prerequisite test, simple regression and multiple regression. The result of research shows that : (1) internship has positive and significant effect on work readiness (tobs 2,371 > ttable 1,990), (2) career guidance has positive and significant effect on work readiness (tobs 2,874 > ttable 1,990), (3) internship and career guidance have positive and significant effect on work readiness (Fobs 14,589 > Ftable 3,11).